Totally Percutaneous Access Using Perclose Proglide for Endovascular Treatment of Aortic Diseases - Saadi,Eduardo Keller (2017)
Abstract Objective: To evaluate our experience following the introduction of a percutaneous program for endovascular treatment of aortic diseases using Perclose Proglide® assessing efficacy, complications and identification of potential risk factors that could predict failure or major access site complications. Methods: A retrospective cohort study during a two-year period was performed. All the patients submitted to totally percutaneous endovascular repair (PEVAR) of aortic diseases and transcatheter aortic valve implantation since we started the total percutaneous approach with the preclosure technique from November 2013 to December 2015 were included in the study. The primary endpoint was major ipsilateral access complication, defined according to PEVAR trial. Results: In a cohort of 123 patients, immediate technical success was obtained in 121 (98.37%) patients, with only two (0.82%) cases in 242 vascular access sites that required intervention immediately after the procedure. Pairwise comparisons revealed increased major access complication among patients with >50% common femoral artery (CFA) calcification vs. none (P=0.004) and > 50% CFA calcification vs. < 50% CFA calcification (P=0.002). Small artery diameter (<6.5 mm) also increased major access complication compared to bigger diameters (> 6.5 mm) (P=0.027). Conclusion: The preclosure technique with two Perclose Proglide® for PEVAR is safe and effective. Complications occur more often in patients with unfavorable access site anatomy and the success rate can be improved with proper patient selection.